2022
DOI: 10.1016/j.bjps.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Breast and abdominal scarring after DIEP flap breast reconstruction: An exploration of patient-reported scar quality

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
(42 reference statements)
0
9
4
Order By: Relevance
“…POSAS scores were inferior in both studies compared to our results, but Siegwart reports a better patients' and observers' overall opinion about scar quality in the DIEP group without mesh [14,36]. Patient information about donor-site scar outcome is crucial to maximize post-operative scar appraisal [14]. Some patients might have the preconception that flap harvesting is equivalent to widely known body-contouring procedures since similar surgical incisions are made, but aesthetic outcome after abdominoplasty has been described as superior to the abdominal donor-site after autologous breast reconstruction [37].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…POSAS scores were inferior in both studies compared to our results, but Siegwart reports a better patients' and observers' overall opinion about scar quality in the DIEP group without mesh [14,36]. Patient information about donor-site scar outcome is crucial to maximize post-operative scar appraisal [14]. Some patients might have the preconception that flap harvesting is equivalent to widely known body-contouring procedures since similar surgical incisions are made, but aesthetic outcome after abdominoplasty has been described as superior to the abdominal donor-site after autologous breast reconstruction [37].…”
Section: Discussioncontrasting
confidence: 91%
“…So far, two studies using the POSAS have been completed for DIEP scar evaluation after breast reconstruction. POSAS scores were inferior in both studies compared to our results, but Siegwart reports a better patients' and observers' overall opinion about scar quality in the DIEP group without mesh [14,36]. Patient information about donor-site scar outcome is crucial to maximize post-operative scar appraisal [14].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…So far, two studies using the POSAS have been completed for DIEP scar evaluation after breast reconstruction. The POSAS scores were inferior in both studies compared to our results, but Siegwart reports a better patient and observer overall opinion about scar quality in the DIEP group without a mesh [13,35]. Patient information about donor site scar outcome is crucial to maximizing postoperative scar appraisal [13].…”
Section: Discussioncontrasting
confidence: 62%
“…In order to allow informed consent, all reconstructive options must be well discussed. Moreover, the quality of the provided information in the counseling process is crucial for postoperative patient satisfaction [13]. A literature review revealed three comparative studies about patient-reported donor site morbidity in autologous perforator flap breast reconstruction, with diverging patient preferences being reported [14][15][16].…”
Section: Introductionmentioning
confidence: 99%